Synthesis of Type-I and Type-II LacNAc-Repeating Oligosaccharides as the Backbones of Tumor-Associated Lewis Antigens - Phang, Riping; Lin, Chun-Hung (Frontiers in Immunology, 2022)
Type-I and Type-II LacNAc are Gal-GlcNAc disaccharides bearing a β1,3- or β1,4-linkage respectively. They exist as the backbones of Lewis antigens that are highly expressed in several cancers. Owing to the promise of developing carbohydrate-based anti-cancer vaccines, glycan synthesis at a large scale is indeed an important task. Synthesis of Type-I and Type-II tandem repeat oligomers has been hampered by the presence of GlcNAc residues. Particularly, N-protecting group plays a determining role in affecting glycosyl donor’s reactivity and acceptor’s nucleophilicity. This review discusses several representative studies that assembled desirable glycans in an efficient manner, such as chemoselective one-pot synthesis and chemoenzymatic methods. Additionally, we also highlight solutions that have been offered to tackle long-lasting problems, e.g., prevention of the oxazoline formation and change of donor/acceptor reactivity. In retrospect of scientific achievements, we present the current restrictions and remaining challenges in this less explored frontier.